Light Rail Transit in the Region of Waterloo: A qualitative examination of urban rail’s effects on real estate, development and urban identities - Cook, Justin (University of Waterloo, 2019)
Transit oriented development has become a staple of contemporary planning practice that is applied in cities throughout the world to help guide the development of sustainable, economic, and social outcomes in urban regions. Widely perceived as a response to automobile centric and urban sprawl inducing design principals of post war planning approaches, transit oriented development is offered as a means of achieving compact urban form that negates many of the issues associated with sprawl. While considerable effort has been undertaken to examine the extent to which transit oriented development affects change on surrounding urban environments, few studies exist that have investigated how social processes interact with transit oriented development to produce the observed effects. This research uncovers underlying social dynamics and perspectives that shape the potential effectiveness of transit oriented development to restructure Canadian real estate markets, urban and economic development trends, and resident behaviour. A case study of the ION light rail transit project in the Region of Waterloo, Ontario, examines how and why resident perspectives and social dynamics are emerging because of the project and subsequently affecting the Region’s development patterns. Focus groups with real estate agents are presented as the primary data of the thesis, which depict the project as a mechanism for attracting creative class economic development and new residents, resulting in an urban landscape divided between automobile and transit centric communities and lifestyles. Findings show the need to increase the use of qualitative methods in transit oriented development research, as they carry the potential to uncover and explain associated trends. To address sustainability, economic development, and social equity concerns related to TOD, recommendations to enact policies that can offset gentrification and unaffordability trends, promote increased behaviour change amongst heterogeneous and automobile centric populations, and to capitalize on homogeneous population preferences are offered.
Keywords: Urban Planning; Transit Oriented Development; Light Rail Transit; Urban Rail; Intensification; Hedonic Modeling; Neighbourhood Change; Residential Markets